(untitled) (PERENNIAL, 2023)
This research aimed to evaluate the bioactivity of liquid smoke from teak leaves to the Schizophyllum commune Fries fungus. The research was conducted in several steps,i.e., pyrolysis of liquid smoke and efficacy test of liquid smoke as an antifungal. The agar media used was PDA (potatoes dextrose agar). The concentration of liquid smoke used for the treatment were 0; 0.25%; 0.50%; 0.75%; 1.00%; 1.25%; and 1.50% (v/v). The results indicated that the liquid smoke inhibited the Schizophyllum commune fungi growth. The concentration of liquid smoke resulted in significantly different antifungal activities. Liquid smoke with a concentration of 1% and 1.25% produced an average antifungal activity of 44.44% with a somewhat resistant category. The contents of organic fractions of liquid smoke, such as acid and phenol, might be responsible for these antifungal activities.